Injection Drug Use-Associated Candidemia: Incidence, Clinical Features, and Outcomes, East Tennessee, 2014–2018. (2nd September 2020) - Rossow, John A; Gharpure, Radhika; Brennan, Julia; Relan, Pryanka; Williams, Sabrina R; Vallabhaneni, Snigdha; Jackson, Brendan R; Graber, Caroline R; Hillis, Sherry R; Schaffner, William; Dunn, John R; Jones, Timothy F
Abstract: Background: Injection drug use (IDU) is an established but uncommon risk factor for candidemia. Surveillance for candidemia is conducted in East Tennessee, an area heavily impacted by the opioid crisis and IDU. We evaluated IDU-associated candidemia to characterize the epidemiology and estimate the burden. Methods: We assessed the proportion of candidemia cases related to IDU during January 1, 2014–September 30, 2018, estimated candidemia incidence in the overall population and among persons who inject drugs (PWID), and reviewed medical records to compare clinical features and outcomes among IDU-associated and non-IDU candidemia cases. Results: The proportion of IDU-associated candidemia cases in East Tennessee increased from 6.1% in 2014 to 14.5% in 2018. Overall candidemia incidence in East Tennessee was 13.5/100 000, and incidence among PWID was 402–1895/100 000. Injection drug use-associated cases were younger (median age, 34.5 vs 60 years) and more frequently had endocarditis (39% vs 3%). All-cause 30-day mortality was 8% among IDU-associated cases versus 25% among non-IDU cases. Conclusions: A growing proportion of candidemia in East Tennessee is associated with IDU, posing an additional burden from the opioid crisis. The lower mortality among IDU-associated cases likely reflects in part the younger demographic; however, Candida endocarditis seen among approximately 40% underscores the seriousness of the infection and need for prevention.